The Relationship between Islamic Business Ethics and Customer Retention: Evidence from Sharia Bank in Ponorogo - Susilo, Adib; Putra, Sadam Maherah Rofiqkhan; Arief, Suyoto; Lesmana, Meichio (El-Barka, 2023)
Customer loyalty would lead to customer retention which in turn would lead to company profit. Sadly, the lack of customer awareness on sharia bank led them to the conclusion that Islamic bank is just the same with the conventional bank. Therefore, this paper is aimed to investigate the relationship between Islamic business ethics of Prophet Muhammad character on customer retention at sharia bank in Ponorogo. Moreover, the research on this field is still few to find. The method employs in this study is quantitative method with exploratory factor analysis (EFA) and multiple regression analysis. The respondent of this study is 129 from the customer of sharia bank in Ponorogo. The data was analysed through SPSS 20 tool. This study found that EFA result indicates that from 4 variables of hypotheses which is based from 4 praiseworthy attributes of the prophet namely, siddiq, tabligh, amanah, and fathanah emerged onto 3 variables namely siddiq, tablig, and fathanah due to amanah variable merged into sidiq variables. Meanwhile, regression analysis found that siddiq (X1), tabligh (X2), and fathanah (X3) partially and simultaneously influence the customer retention (Y). The influences of independent variables on dependent variable are about 65.1%. Further analysis in the future studies is suggested with additional variables such as religiosity or TPB and other variables. Moreover, structural equation modelling (SEM) analysis also suggested for future studies in order to achieve advanced results.